ANALISIS PENGARUH TINGKAT KUALITAS PELAYANAN JASA PUSKESMAS TERHADAP KEPUASAN PASIEN - Rianasari, Virginita (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2019)
This study was conducted to examine the effect of the quality level of Puskesmas services on patient satisfaction. The sample used in this study amounted to 100 respondents. The sampling method uses purposive sampling. The data analysis method used is quantitative analysis using validity and reliability testing, classic assumption test, F test, coefficient of determination, t test and multiple regression analysis. By using multiple regression methods it can be concluded that the direct evidence variable has a positive and significant effect on customer satisfaction with a significance value (P Value) of 0.0030.05. Guarantee has a positive but not significant effect on consumer satisfaction with a significance value (P Value) of 0.164 <0.05. Responsiveness has a positive but not significant effect on customer satisfaction with a significance value (P Value) of 0.339> 0.05. Empathy does not have a positive and insignificant effect on customer satisfaction with a significance value (P Value) of 0.623> 0.05. Simultaneously direct evidence, reliability, assurance, responsiveness and empathy have a significant effect on customer satisfaction with F count of 11,186 with a significance number (P Value) of 0,000 <0,05. The coefficient of determination produced is 0.34, which means that 34 percent of changes in variable customer satisfaction are explained by changes in direct evidence variables, reliability, assurance, responsiveness and empathy together, while the remaining 66 percent is explained by other variables not included in this research.